Religious groups and religious organizations in the Russian Federation: Legal aspects of activity - Kuleshova, Galina (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article provides a legal analysis of the activities of religious groups and religious organizations. Activities of religious organizations are regulated by the Federal Law of 1997 which defines religious organizations as associations of citizens of the Russian Federation, other persons permanently and legally residing in the territory of the Russian Federation, formed for joint confession and dissemination of faith and registered as a legal entity recognized in the Russian Federation. Religious groups are voluntary associations of citizens carrying out activities without state legal registration and acquisition of a legal capacity as a legal entity. The authorʼs work is largely based on regional material.
Keywords: grupy wyznaniowe; organizacje wyznaniowe; regulaminy; państwo prawa